Vibration control of a cylindrical shell with concurrent active piezoelectric patches and passive cardboard liner. (July 2017) - Plattenburg, Joseph; Dreyer, Jason T.; Singh, Rajendra
Abstract: This article extends a recent publication [MSSP (2016), 176−196] by developing a Rayleigh-Ritz model of a thin cylindrical shell to predict its response subject to concurrent active and passive damping treatments. These take the form of piezoelectric patches and a distributed cardboard liner, since the effects of such combined treatments are yet to be investigated. Furthermore, prior literature typically considers only the "bimorph" active patch configuration (with patches on the inner and outer shell surfaces), which is not feasible with an interior passive liner treatment. Therefore, a novel configuration—termed as "unimorph"—is proposed and included in the model. Experiments are performed on a shell with active patches (under harmonic excitation from 200 to 2000 Hz) in both the bimorph and unimorph configurations to provide evidence for the analytical model predictions. The proposed model is then employed to assess competing control system designs by examining local vs. global control schemes as well as considering several alternate active patch locations, both with and without the passive damping. Non-dimensional performance metrics are devised to facilitate comparisons of vibration attenuation among different designs. Finally, insertion loss values are measured under single-frequency excitation to evaluate several vibration control designs, and to compare the effects of alternate damping treatments. Highlights: A thin-shell vibration model with concurrent active and passive damping is developed. A novel active patch configuration is proposed with experimental evidence. A model-based vibration control strategy (global and local control) is proposed. A comparative study is performed for vibration control with experimental results.